Growth direction, position and size of the jaws in open bite of skeletal class II and III malocclusion - Pérez Cahuaya, Lisbeth (2015)
The aim of the study was to determine the growth direction, position and size of the maxilla and mandiblewith skeletal open bite Class II and III. Methodology: This is an observational, descriptive andcross-sectional investigation. The population consisted of 100 lateral cephalometric radiographs of patientswith clinical diagnosis of skeletal open bite. The sample was not probabilistic for convenience. TheNemoceph program was used for Ricketts analysis to get the values of variables. The sample consistedof 36 radiographs of skeletal open bites. The data obtained were analyzed with the chi-square test at aconfidence level of 95% equivalent to 1.96 and a margin of error of 5%. Results: Of the 36 open bites,72.2% were class II and 27.8% Class III skeletal pattern. The two groups showed mostly normodivergentgrowth direction in the maxilla but all the mandibles showed hyperdivergent growth. In relation toposition, both groups had normal position of the maxilla, but differed in size, being normal size for classII group and increased size for Class III. With respect to mandible, both groups showed decreased size,but differences in position, being a retruded position for class II group and a normal position in class IIIgroup. Conclusion: There were no significant difference, p<0.05, in the growth direction, position andsize of maxilla and mandible in skeletal patterns of class II and class III.